A doll's house - McGuinness, Frank (Faber, 1996)
Nora Helmer, wife to Torvald and mother of three children, appears to enjoy living the life of a pampered, indulged child. But as her economic dependence becomes brutally clear, Nora's acceptance of the status quo undergoes a profound change. To the horror of the bewildered Torvald, himself caught in the tight web of a conservative society which demands that he exert strict control, Nora comes to see that only possible true course of action is to leave the family home. Frank McGuinness's version of "A Doll's House" received its London premiere in October 1996 and opened on Broadway in 1997, where the production won four Tony Awards.